ANALISIS CITA RASA, CITRA MEREK DAN EVENT MARKETING TERHADAP KEPUTUSAN PEMBELIAN ES TEH JAWI NGANJUK - pamungkas, Ramadhan dewa; Kusumaningtyas, Dian; Paramitha, Dyah Ayu (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2024)
This study aims to determine the factors that influence purchasing decisions. This research was conducted at Es tea jawi Nganjuk. Purchasing decisions are the dependent variable, the independent variables are taste, brand image, and event marketing. Data is obtained from consumers who buy at Es teh jawi Nganjuk. The minimum number of samples taken was 95 respondents using incidental nonprobability sampling method and sampling technique based on chance. The research method used multiple linear regression analysis techniques using IBM SPSS Statistics software version 2.9. The results of the t test research show that the taste variable, and event marketing partially have a significant effect on purchasing decisions, and the brand image variable partially has no significant effect on purchasing decisions. Based on the results of the F test, it is known that the variables of taste, product image, and event marketing simultaneously have a significant effect on purchasing decisions. It is recommended that Nganjuk jawi ice tea pay more attention to taste factors, product image, and event marketing so that purchasing decisions increase.